2016
DOI: 10.1590/s1980-6574201600040002
|View full text |Cite
|
Sign up to set email alerts
|

Vasculopathy associated with peripheral neuropathy in gait parameters of diabetic people

Abstract: -Diabetic peripheral neuropathy (DPN) is a common complication of diabetes mellitus when glycemic levels are poorly controlled. Sometimes DPN is accompanied by vasculopathy (DPV), which can worsen the clinical prognosis. The aim of this study was to analyze the gait parameters of nondiabetic individuals and diabetic individuals with DPN with or without DPV. Method: The study included 68 individuals (50 to 65 years old) divided into three groups: people without diabetes mellitus (n = 33), diabetic patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Children are currently encouraged to exercise for at least 60 minutes a day to reduce the risk of vascular complications [21,22]. Children with T1DM may undertake most types of physical activity, especially if its intensity ranges from 40 to 56% of VO 2max or 55-69% of maximum heart rate [23,24]. In our questionnaire, 72.8% of physiotherapists knew the physical activity amount for T1DM patients, its impact on their bodies (81.6%) and the contraindications (82.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Children are currently encouraged to exercise for at least 60 minutes a day to reduce the risk of vascular complications [21,22]. Children with T1DM may undertake most types of physical activity, especially if its intensity ranges from 40 to 56% of VO 2max or 55-69% of maximum heart rate [23,24]. In our questionnaire, 72.8% of physiotherapists knew the physical activity amount for T1DM patients, its impact on their bodies (81.6%) and the contraindications (82.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Os integrantes foram recrutados para um centro de reabilitação física de uma universidade de Presidente Prudente e quando se enquadraram nos critérios de inclusão foram submetidos a uma avaliação (AV1), o qual foram inicialmente questionados sobre informações sociodemográficas e posteriormente foram submetidos a uma avaliação das variáveis antropométricas (altura e peso) e da pressão plantar na Fisioterapia Brasil 2022;23(3):402-414 plataforma de baropodometria eletrônica de dois metros de comprimento (FootWalk Pro®, AM CUBE, França) com frequência de amostragem de 200 Hz [14].…”
Section: Métodosunclassified
“…Pataky et al [ 21 ] reported a significant correlation between plantar pressure under the first metatarsal head and Doppler arterial pressure of both tibial posterior and dorsalis pedis artery in diabetic patients with both peripheral neuropathy and vascular disease. Mantovani et al [ 22 ] reported a higher pressure-time integral in diabetic patients with both peripheral neuropathy and peripheral vasculopathy compared with nondiabetic patients. They suggested that the gait pattern worsened with the severity of clinical impairment.…”
Section: Introductionmentioning
confidence: 99%